The Implementation of Iqab for Islamic Boarding School Students - Tanjung, Rani Nurisa; Nahar, Syamsu; Rakhmawati, Fibri (Jurnal Basicedu, 2023)
The implementation of rules in the classroom, including the imposition of punishment (iqab), can help students develop their personalities. In this study, the 'iqab program for elementary school children at the Darul Hikmah Islamic boarding school, Asahan Regency, will be described. A qualitative methodology and phenomenological approach are used in this investigation. employing observation, interviews, and documentation studies to gather data. data analysis that includes data display, data reduction strategies, and conclusion-making. The findings of this study show that: (1) the academic guidebook for pupils serves to socialize the idea of the "iqab"; (2) The purpose of implementing the 'iqab is to educate and stimulate students, thereby motivating them to behave well, maintain discipline, and abide by the law. Penalties must also have a high priority on benefits for pupils' education; (3) The diverse backgrounds of the students, the need for repeated warnings to get them used to following the rules of the pesantren, the students' lack of awareness, and the lack of cooperation between parents/guardians and the pesantren in maximizing the implementation of the rules are all obstacles to the implementation of iqab, and (4) The pesantren asks parents and guardians of students to assist in applying 'iqab, as well as to observe and assess the implementation each time a sanction is given to demonstrate the efficacy of enforcing sanctions on students, in order to overcome hurdles to doing so.